Hydrogen inhalation in rehabilitation program of the medical staff recovered from COVID-19 - L. V. Shogenova (Кардиоваскулярная терапия и профилактика, 2021)
Active hydrogen inhalation (H(H2O)m) has powerful antioxidant and antiapoptotic effects. In recent years, it has been used in a number of experimental and clinical studies.Aim. To study the safety and effectiveness of inhalation of the “active form of hydrogen” (AFV;(H(H2O)m)) in the rehabilitation program of coronavirus disease 2019 (COVID-19) survivors during the recovery period.Material and methods. This randomized controlled parallel prospective study included 60 COVID-19 survivors with post-COVID-19 syndrome (ICD-10: U09.9) during the recovery period, with clinical manifestations of chronic fatigue syndrome (CFS), who received standard therapy in accordance with the management protocol of patients with CFS (ICD-10: G93.3): physiotherapy and medication therapy with drugs containing magnesium, B vitamins and L-carnitine. The patients were divided into 2 groups. The experimental group (n=30) included patients who received hydrogen inhalation for 90 minutes every day during 10 days (SUISONIA hydrogen inhalation device, Japan). The control group (n=30) consisted of patients who received standard therapy. In both groups, patients were comparable in sex and mean age: in the experimental group — 53 (22; 70) years, in the control group — 51 (25; 70) years. Biological markers of systemic inflammation, oxygen transport, lactate metabolism, intrapulmonary shunting, 6-minute walk test, and vascular endothelial function were determined in all patients on the 1st and 10th days of follow-up.Results. In the experimental group, a decrease in following parameters was revealed: stiffness index (SI), from 8,8±1,8 to 6,8±1,5 (p<0,0001); ALT, from 24,0±12,7 to 20,22±10,61 U/L (p<0,001); venous blood lactate, from 2,5±0,8 to 1,5±1,0 mmol/L (p<0,001); capillary blood lactate, from 2,9±0,8 to 2,0±0,8 mmol/L (p<0,0001); estimated pulmonary shunt fraction (Qs/Qt, Berggren equation, 1942) from 8,98±5,7 to 5,34±3,2 (p<0,01); white blood cells, from 6,64±1,57 to 5,92±1,32 109/L. In addition, we revealed an increase in the refractive index (RI) from 46,67±13,26% to 63,32±13,44% (p<0,0001), minimum blood oxygen saturation (SpO2) from 92,25±2,9 to 94,25±1, 56% (p<0,05), direct bilirubin from 2,99±1,41 to 3,39±1,34 pmol/L (p<0,01), partial oxygen tension (PvO2) from 26,9±5,0 to 34,8±5,6 mm Hg (p<0,0001), venous oxygen saturation (SvO2) from 51,8±020,6 to 61,1±018,1% (p<0,05), partial capillary oxygen tension (PcO2) from 48,7±15,4 to 63,8±21,2 mm Hg (p<0,01), capillary oxygen saturation (ScO2) from 82,2±4,2 to 86,2±4,8% (p<0,01), distance in 6 minute walk test from 429±45,0 to 569±60 m.Conclusion. Inhalation therapy with H(H2O)m in the rehabilitation program of COVID-19 survivors during the recovery period is a safe and highly effective method. Manifestations of silent hypoxemia and endothelial dysfunction decreased, while exercise tolerance increased. As for laboratory tests, a decrease in the white blood cell count, estimated pulmonary shunt fraction and lactate content parameters was revealed.